Green Marketing Strategies in Circular Economy Startups in Indonesia: A Grounded Theory Approach - Muh Fajrul; Erlitawati Kaharudin; Herlin Hidayat; Hesti Fajarsari; Alexander Nova Vernando (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2026)
Abstract. Indonesia's transition to a circular economy (CE) faces persistent barriers, including low public awareness and consumer distrust in green claims, posing distinct marketing challenges for resource-constrained CE startups. This study develops a context-specific green marketing strategy model for CE startups in Indonesia. A grounded theory approach was employed, with data collected through in-depth interviews with 15 participants (startup founders, marketing team members, and consumers) along with document analysis and participatory observation of five CE startups in Java. Open, axial, and selective coding were conducted using NVivo 14. Four interdependent strategic pillars were identified: radical transparency in production and environmental impact disclosure, continuous consumer education on CE principles, strategic ecosystem collaboration with NGOs and green influencers, and authentic founder-centered storytelling. These pillars constitute the Circular Green Marketing Framework, integrating circular values into branding and marketing communication. Theoretically, this study enriches green marketing literature from a Global South perspective, advancing signaling theory and legitimacy theory in resource-constrained startup contexts. Practically, the framework offers a replicable roadmap for CE startups to build brand differentiation, counter greenwashing perceptions, and cultivate consumer loyalty without substantial marketing budgets.